Time-lapse imaging of human embryos fertilized with testicular sperm reveals an impact on the first embryonic cell cycle. Issue 6 (4th March 2021) - van Marion, E S; Speksnijder, J P; Hoek, J; Boellaard, W P A; Dinkelman-Smit, M; Chavli, E A; Steegers-Theunissen, R P M; Laven, J S E; Baart, E B
Abstract: Testicular sperm is increasingly used during in vitro fertilization treatment. Testicular sperm has the ability to fertilize the oocyte after intracytoplasmic sperm injection (ICSI), but they have not undergone maturation during epididymal transport. Testicular sperm differs from ejaculated sperm in terms of chromatin maturity, incidence of DNA damage, and RNA content. It is not fully understood what the biological impact is of using testicular sperm, on fertilization, preimplantation embryo development, and postimplantation development. Our goal was to investigate differences in human preimplantation embryo development after ICSI using testicular sperm (TESE-ICSI) and ejaculated sperm. We used time-lapse embryo culture to study these possible differences. Embryos (n = 639) originating from 208 couples undergoing TESE-ICSI treatment were studied and compared to embryos (n = 866) originating from 243 couples undergoing ICSI treatment with ejaculated sperm. Using statistical analysis with linear mixed models, we observed that pronuclei appeared 0.55 h earlier in TESE-ICSI embryos, after which the pronuclear stage lasted 0.55 h longer. Also, significantly more TESE-ICSI embryos showed direct unequal cleavage from the 1-cell stage to the 3-cell stage. TESE-ICSI embryos proceeded faster through the cleavage divisions to the 5- and the 6-cell stage, but this effect disappeared when we adjusted our model for maternal factors. In conclusion, sperm origin affects embryo development during the first embryonic cell cycle, but not developmental kinetics to the 8-cell stage. Our results provide insight into the biological differences between testicular and ejaculated sperm and their impact during human fertilization. Abstract : Human embryos originating from fertilization with testicular sperm show a prolonged pronuclear stage and more often direct unequal cleavage than embryos originating from ejaculated sperm, while subsequent cleavage divisions are not impacted.